Student Perception of Thermal Comfort of Outdoor Space in Nusa Nipa University, Maumere, East Nusa Tenggara - HILDEGARDIS, CORNELIA -; Saraswati, Anak Agung Ayu Oka; Diasana, I Dewa Gede Agung; Dewi, Ni Ketut Agusinta (International Journal of Engineering and Emerging Technology; Vol 4 No 2 (2019): July - DecemberDO - 10.24843/IJEET.2019.v04.i02.p04, 2020)
Nusa Nipa University is one of a number of universities in Maumere City, Sikka Regency, East Nusa Tenggara. Based on the Koppen climate classification, the City of Maumere is included in the savanna. The savanna climate is different from the tropical rain climate in terms of temperature, air humidity and wind speed. The high temperature in this city influences the perception of thermal comfort. Thermal comfort is a necessity for people performing activities in both outside and inside of building, one of those are students at Nusa Nipa University. This research was conducted by distributing questionnaire to 50 students occupying in 2 (two) different spots in the outdoor space. The result showed that 58% students felt comfortable in the grassy area with shade compared to other off-campus areas. This perception of comfort is influenced by comfort factors namely hardscape or softscape that exist in the outdoor space of the Nusa Nipa University.